Predictive validity of laboratory-based physiological variables for running and cycling time-trial performances in male sub-elite triathletes - Suppiah, H. T. (Journal of Australian Strength and Conditioning, 2019)
Ventilatory threshold was better able to predict 10km running and 40km cycling performance with sub-elite level male triathletes as compared to the lactate threshold.